Imam al-Muqri and His Contributions in the Field of Jurisprudence Rules - Benmokeddem, Messaouda Ibrahim (Journal of Islamic Sciences, 2020)
The Imam (Al-Muqri Al-Jid) is considered one of the scholars of the MalikiFiqhSchool, which made every effort in his service, especially in the field of jurisprudence rules, where he worked through his groups to formulate jurisprudence in the form of precise rules to facilitate its use and facilitate reference to it. Although it is one of the most important sources of jurisprudence with abundance, benefit and simplicity of its style, it has not received much attention from students of this science and its followers, in the past and present. Therefore, I intend in this article to explain the contributions of the imam, may God have mercy on him, in the field of rules of jurisprudence, which enriched the Maliki Fiqh library, in the first part of the search, I got to know Imam al-Maqri, including the era which he lived, and in relation to the second part: I spoke about the subject of jurisprudence rules as a stand-alone science, then I spoke about his contributions at the end of the research, I followed in this research the descriptive method, as it is consistent with this type of studies, with regard to the description of Imam al-Maqri, as well as his works in the field of jurisprudence.
Keywords: Al-Maqri the grandfather; AL-Maliki Fiqh; Jurisprudence Rules; Contributions